Concentrações de metais pesados por espectometria de emissão ótica com plasma induzido e caracterização dos solos do cemitério Padre Arthur Vangeel, Francisco Beltrão (PR) - Ribeiro, Raoana de Souza (2021)
Many environmental and public health impacts are caused by the misallocation of cemeteries, especially when implemented without planning followed by legislation. This project aimed to evaluate the soil of the Padre Arthur angeel municipal cemetery of Francisco Beltrão, located in southwestern Paraná. The investigation started through past works which found pollutants in the Lonqueador River, located near the cemetery, which may come from the decomposition of corpses and materials present in the coffins. Thus, 32 samples were collected at 15 points in and around the cemetery, with volumetric rings collected in duplicates in the depth of 20 cm and with the Dutch auger about 50 cm for chemical, physical and biological analyses. Quantitatively, a low level of basal soil respiration was found, thus representing a low metabolic activity by microorganisms. Using the Induced Plasma Optical Emission Spectrometry (ICP-OES) technique, it is possible to verify the presence of heavy metals as Al, As, Cr, Cu, Fe, Mn, Ni, Pb and Zn with higher aluminum contents and lower levels of lead present in the soil inside the cemetery, being in compliance with CONAMA resolution 420 but not in accordance with the CONAMA resolution 335.